The Distribution And Population Of Chiltan Wild Goat (Capra Aegagrus Chialtanensis) In Its Last Remaining Refuge Of Hazarganji Chiltan National Park Balochistan, Pakistan - Baloch, Sharif-Ud-Din (2013)
Chiltan wild goat (Capra aegagrus chialtanensis) is one of the important sub-species of wild goats founds in Balochistan and endemic to Hazarganji Chiltan National Park. Previously it was found in Koh-i-Murdar, Koh-i-Maran and Koh-i- Gish but due to ruthlessly poaching, habitat loss and competition with domestic livestock all population of Chiltan wild goat locally extinct from the areas. For the protection of Chiltan wild goat and its habitat, the areas of Hazarganji State Forest and Chiltan Protected Forest were declared as National Park on 15 January 1980. There is common agreement that no ungulate population remains static. The present study was conducted after 2008 in the rut season of Chiltan wild goat until November 2012 to document the distribution of Chiltan wild goat in its last remaining refuge, to investigate its population, behaviors and potential threats. The data were collected by using fixed point survey method (vantage point). During the study 984 Chiltan wild goats with distribution of 431 (44%) in Hazarganji area, 401 (41%) in Chiltan area and 152 (15%) in Tal, Haider and Surkho areas were observed. The results of present study revealed that on average the population of Chiltan wild goat is significantly increasing with population growth rate of (8.25%) for the last ten years (1992-2012). Moreover the male, female, kids and yearlings were observed with population growth rate of (9.22%), (6.93%), (8.44%) and (9.91%) respectively.